"Poetry, Like Bread is for Everyone" An Essay on Stanzas and Status. Issue 1 (2nd April 2020) - Sernaker, Emily
Abstract: This paper examines what it takes to call yourself "a poet" through the lens of inclusive programming at Brooklyn Public Library.